SELF-MOTIVATION IN IMPROVING LIBRARIAN PERFORMANCE AT UNIVERSITAS SARI MUTIARA INDONESIA LIBRARY - Tiara Rachellya; Nurhayani Nurhayani (JUPIIS: JURNAL PENDIDIKAN ILMU-ILMU SOSIAL, 2023)
Self-motivation is the driving force behind taking action and achieving high performance. An individual must be motivated by his own desire to pursue the goals of the organization or agency. The problem in this study is how to describe self-motivation in improving the performance of librarians in the library of Sari Mutiara University, Indonesia. The purpose of this study was to determine the role of self-motivation in improving the performance of librarians in the library of Sari Mutiara University of Indonesia. In this study, the research approach to be carried out is qualitative research with a descriptive approach. This research method aims to precisely describe individual traits, circumstances, and other factors to solve problems. The result of this study is that the self-motivation of librarians at the University of Sari Mutiara Indonesia Library is formed from motivational factors supported by hygiene factors. This can be seen from the work achievements achieved by librarians, the recognition of their existence as librarians, completing the work given, having a great sense of responsibility, and the desire to develop their potential. In addition, other things that support the magnitude of self-motivation of librarians in improving performance are policies and administration that do not burden librarians, harmonious relationships between fellow librarians, income that can meet the needs of life, evaluations aimed at performance appraisals, and pleasant, comfortable, and conducive workplace conditions.